2017
DOI: 10.1007/s40653-017-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Recalling a Devastating Tornado: Qualities of Child Recollections and Associations with Mental Health Symptoms

Abstract: Trauma recollections often contain trauma-related cognitive and emotional processing. Research examining indicators of such processing in children's trauma recollections and their association with mental health symptoms is limited. Fifty 8 to 12-year-old children provided two open-ended recollections about (1) challenging/"bad" things and (2) positive/ "good" things that happened to them 1-year post experiencing an EF-5 tornado. Children completed exposure and mental health symptom measures (PTSD, anxiety, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In children, a combination of attributions, particularly meaning-seeking and perceived tornado exposure, were overall predictors of long-term distress after a tornado [ 27 ]. In addition, children’s emotional processing was found to impact children’s meaning-making efforts and have implications for their adjustment after a tornado [ 23 , 41 ]. Finally, maternal support was found to be important in the relationship between children’s use of both positive and negative emotional language and child tornado-related post-traumatic stress syndrome (PTSS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, a combination of attributions, particularly meaning-seeking and perceived tornado exposure, were overall predictors of long-term distress after a tornado [ 27 ]. In addition, children’s emotional processing was found to impact children’s meaning-making efforts and have implications for their adjustment after a tornado [ 23 , 41 ]. Finally, maternal support was found to be important in the relationship between children’s use of both positive and negative emotional language and child tornado-related post-traumatic stress syndrome (PTSS).…”
Section: Resultsmentioning
confidence: 99%
“…Greater severity of tornado exposure was also associated with alcohol use by adolescents [ 16 , 31 ]. However, two studies found that tornado exposure was unrelated to child-reported emotions and mental health symptoms after a tornado [ 23 , 41 ]. Tornado Exposure Questionnaire, The Tornado-Related Traumatic Experiences Questionnaire, and Natural Disaster Experiences Inventory were used to measure the severity of tornado exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In general, more coherent recollections have been thought to be indicators of better psychological adjustment and well-being (Baerger & McAdams, 1999; Waters & Fivush, 2015). However, emerging literature has suggested that more coherent trauma recollections are not universally signs of good adjustment and that coherence may be associated with elevated mental health problems in some circumstances (e.g., Hambrick, Vernberg, Greenhoot, & Hendrickson, 2018). For example, Hambrick et al (2018) found that among a community sample of children exposed to a devastating tornado in Joplin, Missouri, coherent recollections were associated with increased mental health symptoms when children discussed bad things that happened during the tornado.…”
Section: Narrative Research and Recollection Qualities In Youthmentioning
confidence: 99%
“…How much, and which details, of the event are recollected may indicate whether individuals are avoiding, or becoming overengaged with, anxiety-provoking aspects of the event (Hambrick, 2014; Mossige, Jensen, Gulbrandsen, Reichelt, & Tjersland, 2005). For example, interpretive statements that reference personal impact may represent how an individual is currently understanding a stressful or traumatic event in relation to his or her personal beliefs, goals, and subjective sense of purpose (Greenhoot et al, 2013; Hambrick et al, 2018; Park, 2010). Discussion of personal impacts of the event may include references to psychological or relational impact of the event on the narrator for better or worse (Greenhoot et al, 2013).…”
Section: Narrative Research and Recollection Qualities In Youthmentioning
confidence: 99%
See 1 more Smart Citation